The Effect of Transfer Pricing, Thin Capitalization and Foreign Ownership on Tax Aggressiveness in Manufacturing Companies in Indonesia - Puspita, Desi Ayu; Parwati, Ni Made Suwitri; Yuniar, Latifah Sukmawati; Furqan, Andi Chairil (E-Jurnal Akuntansi, 2025)
This study aims to analyze the effect of transfer pricing, thin capitalization, and foreign ownership on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Secondary data was obtained from an annual report with a sample of 39 companies selected through the purposive sampling method, resulting in 195 observations. Data analysis was carried out using the help of WarpPLS 8.0 software. The results of the study showed that transfer pricing did not have a significant effect on tax aggressiveness, while thin capitalization and foreign ownership were proven to have a significant positive effect. These findings support the agency's theory that managers tend to act opportunistic in reducing tax burdens through capital structure policies and foreign shareholder encouragement. This research contributes to enriching the literature on tax avoidance practices in Indonesia and provides implications for regulators to strengthen tax regulations and supervision.